ปัจจัยที่ส่งผลต่อการพัฒนาอาคารชุดตามแนวรถไฟฟ้าขนส่งมวลชนในกรุงเทพมหานคร - กฤติญา นิมมานรดี (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Bangkok rail transit systems, the Bangkok Transit System (BTS) and the Mass Rapid Transit (MRT) subway, which began operations in 1999 and 2004, respectively, have not only helped to ease the severe traffic problems in Bangkok, but also greatly influenced land value and property development along the transit corridors. High-density residential development, i.e. condominium, is particularly rapid and intense near many transit stations. The objective of this research is to examine the effect of rail transit systems on the pattern of condominium developments that have changed significantly since the introduction of the systems and study the various factors that affect such pattern, including land ownership, plot sizes of land, zoning control, and road network in the area. Obtaining secondary data from various sources, we put together a database of condominiums located within 500 meters radius of rail transit stations in Bangkok. We used linear regression technique to analyze and explain the relationship between these variables. From analysis to factors, the factors according to plot sizes of land, road network, land value, and government policy provide significantly effect on the number of condominium and condominium’s unit. The results would be useful for developing transportation land use model, which is an important component of urban transportation planning process.